Level of Effectiveness for ERP System in Improving the Educational Process in Higher Education Institutions in Yemen: A Case Study of the University of Science and Technology - Mohammed Ali AL-Mandi; Abdulrahman AL-Sharjabi (University of Science and Technology, Yemen, 2020)
This study aimed to identify the level of effectiveness of the Enterprises Resource Planning (ERP) in improving the educational process in higher education institutions in Yemen. The case study was carried out in the University of Science and Technology (UST). The study adopted the analytical descriptive method, using a questionnaire, which was distributed to the whole population (90 employees), who deal with the ERP system at the university, and who were selected by the complete census method. Only 74 questionnaires were returned and were subject to statistical analysis. Major findings revealed that there was a statistically significant correlation between the dimensions of the questionnaire and the overall effectiveness of the ERP system at the university. Therefore, this result indicates that there is a high degree of effectiveness of the ERP system in improving the educational process with a high agreement score on the dimensions of the questionnaire. It was found that the highest effectiveness degree was in the dimension of admission and registration support, followed by academic support and student affairs, and the lowest degree was in the dimension of technical support. Overall, the level of application of the ERP system at the university was high. Based on these findings, it was recommended that this system should be applied so as to cover all departments that do not use the ERP system, which would lead to effective and efficient performance of such departments.